Analisis Pengaruh Belanja Sektor Kesehatan Terhadap Angka Harapan Hidup Di Sumatera Utara - Yuditya Nasution; Lailan Safina Hasibuan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
In increasing economic growth in an area, a dominant role is needed bythe government in the area, where the government is spending in thehope that the greater the amount of government spending, the greaterthe economic growth of the region. The Human Development Index(HDI) in which there is a component of life expectancy is one of themeasuring tools in looking at economic growth in an area. If the lifeexpectancy in an area is higher then the level of productivity of thepeople in the area is also higher followed by an increase in income percapita which increases the purchasing power thus spurring theeconomic growth of the region. The purpose of this study was toexamine the effect of government health spending in the health sectoron life expectancy in the province of North Sumatra. The data used areNorth Sumatra government expenditure data in the field of health andlife expectancy data in North Sumatra with the 2006-2014 base yearobtained from the North Sumatra BPS and the Ministry of Health. Theresults of the Klassen Typology show that the relationship betweenhealth sector spending and life expectancy in the North Sumatraprovincial district / city that which area is included in the high percapita expenditure category and where the area of life expectancy islow.